Perseverance, partnerships and passion: ingredients for successful local government policy to promote healthy and sustainable diets - Liza R. Barbour; Julie L. Woods; Julie K. Brimblecombe (BMC, 2023)
Abstract Background Local government authorities are well-placed to invest in evidence-based food policies that promote a population-wide shift to healthy and sustainable diets. This study describes the contextual factors that facilitated or impeded policy-making related to healthy and sustainable diets within a 'best-performing' local government in Victoria, Australia. Methods Guided by the Consolidated Framework for Implementation Research (CFIR), data from semi-structured interviews with individuals involved in developing the City of Greater Bendigo's Food System Strategy were analysed using the seven-stage Framework Method. Results Semi-structured interviews (n = 24) were conducted with City of Greater Bendigo employees (n = 15) and key stakeholders working for local organisations (n = 6) or at a state or national level (n = 3). Interviewees mostly held positions of leadership (n = 20) and represented diverse areas of focus from health (n = 7), food systems (n = 4) and planning and public policy (n = 3). Data analysis revealed 12 cross-cutting themes; eight facilitating factors and four impeding factors. Facilitating factors included perseverance, community engagement, supportive state policy, effective leadership, a global platform and networks, partnerships, workforce capacity and passion, and the use of scientific evidence. Impeding factors included access to secure, ongoing financial resources, prohibitive state and federal policy, COVID-related disruptions to community engagement and competing stakeholder interests. Overall, this study suggests that the City of Greater Bendigo's success in developing an evidence-based local food system policy is built upon (i) a holistic worldview that embraces systems-thinking and credible frameworks, (ii) a sustained commitment and investment throughout the inner-setting over time, and (iii) the ability to establish and nurture meaningful partnerships with community groups, neighbouring local government areas and state-level stakeholders, built upon values of reciprocity and respect. Conclusions Despite insufficient resourcing and prohibitive policy at higher levels of government, this 'best performing' local government in Victoria, Australia developed an evidence-based food system policy by employing highly skilled and passionate employees, embracing a holistic worldview towards planetary health and harnessing global networks. Local government authorities aspiring to develop integrated food policy should nurture a workforce culture of taking bold evidence-informed policy action, invest in mechanisms to enable long-standing partnerships with community stakeholders and be prepared to endure a 'slow-burn' approach.